Digital Trust Gap: The differences in perceptions of trust between experienced and inexperienced users - Kim, Gwangjae; Lee, Jee Young (Journal of Telecommunications and the Digital Economy, 2020)
This study examines the relationship between an information and communication technology (ICT) environment developed by strong national policy and the level of user trust in cyberspace in South Korea, using a secondary data analysis of a national survey dataset. We categorised a subsample into the following types of online activities: ‘content creation’, ‘transaction’ and ‘communication’. Each category was analysed by the types of information and the users’ experience while using the internet. The results revealed that the more internet experience a user had, the less they trusted information in cyberspace. In contrast, less experienced users perceived information in cyberspace to be more trustworthy. This was especially evident during transaction and content creation activities. These results differ from existing studies, which showed that developments to the ICT environment with increased internet usage were strongly correlated with increased trust. We present some suggestions drawn from the results of this study that focus on online trust in relation to the ICT environment.